(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Introduction: This study investigates the food patterns and dietary habits of female traders and their influence on the nutritional well-being of children aged 1-36 months in selected markets in Ibadan, Oyo State, Nigeria. The demanding nature of trading activities often affects the dietary routines of female traders, potentially impacting the feeding practices and nutritional status of their infants and children. Objective: The objective of this study is to assess the lifestyle and dietary patterns of female traders and their children and to analyze the factors influencing these patterns. The study aims to provide insights into the nutritional status of children in relation to their mothers’ dietary habits and market-related lifestyle. Method of Data Analysis: Data were collected using a well-structured questionnaire and direct, face-to-face administration. Anthropometric measurements were conducted to assess the nutritional status of children aged 1-36 months. Descriptive statistics and chi-square tests were employed for data analysis using SPSS version 24.0. Results: The study found diverse dietary patterns among female traders, influenced by socio-economic factors and cultural beliefs. In Bodija market, 55.3% disagreed with long work hours compared to 38.7% in Ogunpa. Also, 3.3% in Bodija agreed on low income versus 14% in Ogunpa. Cultural beliefs affected food choices, with 42% in Bodija and 50.7% in Ogunpa citing influence. Food taboos impacted 51.4% in Ogunpa and 33.3% in Bodija. Normal-weight children prevailed in both markets, with variations in underweight and overweight proportions. Boys showed slightly higher overweight rates. Chi-square tests revealed significant associations between food patterns and wasting (Bodija: x2 = 34.175, p = .000*) and underweight (Bodija: x2 = 30.534, p = .000*). In Ogunpa, no significant associations were found for wasting (p = .576) or underweight (p = .988), suggesting varied influencing factors across markets. Conclusion: The findings underscore the importance of tailored interventions and nutritional education programs to address specific dietary needs and challenges among market communities. Efforts to enhance maternal literacy and promote healthy eating practices are crucial for improving the nutritional status of children in these settings. Collaboration between government agencies, community organizations, and healthcare providers is essential for implementing effective interventions and promoting overall well-being among market-goers and their children.